Percutaneous coronary interventions in patients with left main coronary artery pseudobifurcation lesions: 5-years follow-up. (14th October 2021) - Maximkin, D; Shugushev, Z; Faybushevich, A; Chepurnoy, A; Volkov, S; Gitelzon, E; Korobkov, A; Bagin, S; Veretnik, G; Bolivougui, J M
Abstract: Aims: To increase the effectiveness of percutaneous coronary interventions (PCI) in patients with ostium coronary artery lesions: left arterial descending (LAD) or left circumflex (LCx) – pseudobifurcations. Methods: 220 patients were included in the study. Inclusion criteria: ostium atheroslerotic lesions of left arterial descending (LAD) or left circumflex (LCx) >70% according to angiography and optical coherence tomography (OCT); myocardial ischemia according the FFR measurement. According OCT data, all patients were devoiced into 2 groups. In I group (n=110) according to OCT, atherosclerotic plaque spread from the ostium of LAD and/or LCx to the left main coronary artery (LMCA), and in group II (n=110) - the plaque did not spread into the LMCA. In Group I all patients were initially treated with "Provisional T" stenting of the LMCA, and in Group II – precision stenting of the ostium LAD or LCx. Primary endpoints: frequency of MACE (death, MI, revascularizations). Results: The long-term results after 5-years were observe in 98 patients from group I and 92 patients from group II. The survival rate of patients from group I and II, free from cardiac events, were 94.9±4.03 and 81.5±3.23, respectively (p<0.001). Cardiac death were observed in 2 (2.04%) patients from group I and 2 (2.17%) patients from group II (p>0.05). Myocardial infarction were observed in 2 (2.04%) patients from group I and 5 (5.43%) patients from group II (p>0.05). The target lesion revascularization (TLR) was performed in 3 patients (3.06%) in group I, and in 12 patients (13.04%) in group II (p<0.001). The total incidence of MACE were 5.2% in group I and 18.5% in group II (χ 2 =7.825; p=0.023). Conclusions: OCT-guiding analysis of ostium LAD or LCx could be help in choosing the optimal stenting technique, as well as reliably improve long-term PCI results. However, despite the use of intravascular imaging techniques during PCI, precision stenting of the ostium LAD or LCx, differs worst long-term prognosis of patients. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian academic excellence project 5-100